Systematic studies of orchid genus Coelogyne in Peninsular Malaysia - Yoh, Kok Hon (2019)
Coelogyne is a large genus of about 200 species distributed at pantropical area from the Himalayas, Sri Lanka, India, Southern China and throughout South East Asia to the Papua New Guinea. Most of the species are epiphytic which occur on the large tree of primary forest. In Peninsular Malaysia, this poorly studied group of orchids have fairly large number of small, medium to large-sized flowers with pleasant fragrance, but the flowers are usually short-lived. In this study, 59 Coelogyne taxa were collected throughout Peninsular Malaysia and 57 of them were identified to species level. The widely accepted classification system previously was exclusively based on floral morphology, and there were no significant molecular studies of Coelogyne that have been carried out in Peninsular Malaysia so far. To study the phylogeny of this genus, morphology characters were utilized together with molecular evidences to generate the systematic hypotheses. The morphological analysis part was performed using both the vegetative and floral characters. Clustered analysis was conducted on morphological data of 22 different species while the molecular cladistic analyses were carried out for the 59 taxa. DNA extraction, PCR amplification and sequencing was performed on the 59 taxa using the four nucleotide sequence datasets from two distinct genomes, such as chloroplastid genes (rbcL, matK and trnL-F) and nuclear ribosomal gene (nrITS). The resulted sequences from each dataset were used to construct independent and combined cladograms using the Neighbour Joining (NJ) and Maximum Likelihood (ML) methods. The overall morphological analysis showed that three sections of Peninsular Malaysian Coelogyne, i.e. Longifoliae, Speciosae and Fuliginosae were sister groups which closely related than with the other sections by forming one clade. While another clade consisted of four other sections, namely Flaccidae, Coelogynae, Tomentosae and Verrucosae. The molecular systematics analysis had given a robust estimation on the phylogenetic relationships of Coelogyne, which implied that the molecular markers rbcL, matK and trnL-F and nrITS are reliable for the systematics studies of Coelogyne species in Peninsular Malaysia. Even though individual marker was insufficient to solve the evolutionary relationship of a whole genus, but the combination of chloroplastid markers (rbcL, matK and trnL-F) and nrITS which from different regions greatly improved the systematic study. Combined molecular data has significantly provided better resolution by producing more resolved trees and stronger bootstrap support. Molecular evidences supported the result reported in morphological analysis where sections Longifoliae, Speciosae and Fuliginosae were closely related as well as sections Tomentosae and Verrucosae. Section Flaccidae and Coelogynae were placed further from other sections in the phylogenetic tree. Moreover, SCAR markers were also developed from RAPD fragment (Primer: OPU 08 and OPU 12) to discriminate and authenticate three valuable and rare Coelogyne species which are endemic to Peninsular Malaysia, namely Coelogyne kaliana, C. stenochila and C. tiomanensis. These three Coelogyne spp. are highly similar in their vegetatively morphology and difficult to distinguish without the reproductive structure. Three SCAR markers were successfully developed in this study. SCAR marker pair, CKL_f / CKL_r was specific to C. kaliana where it produced a unique single band of 271 bp but not in C. stenochila and C. tiomanensis. Whereas SCAR marker pair CST_f / CST_r amplified a single band of 854 bp in C. stenochila and two bands of different sizes (372 bp and 858 bp) for C. tiomanensis but no amplification in C. kaliana. The third SCAR marker pair, CTI_f / CTI_r produced a single band (about 500 bp) for both C. stenochila and C. tiomanensis but showed no amplification in C. kaliana. Although not all SCAR markers are species specific, but combination of the three SCAR markers can efficiently discriminate among these three Coelogyne species. The accurate identification provides better understanding of the species and allow proper management plan to be established in the effort of conservation.